Analisis Peran Teknologi Berdasarkan Perspektif Merdeka Belajar - Savitri, Aini Shifana; Sholih, Jamilla Agustin Ummu; Herlambang, Yusuf Tri (Indo-MathEdu Intellectuals Journal, 2023)
Technology has an important role in education today. The implementation of this research is about how educators understand the concept of independent learning in applying educational technology as a basis for learning. This research aims to describe the role of technology based on an independent learning perspective. The method in this research uses a qualitative descriptive method. The data collection technique involves conducting a literature review on 20 journals. The research results explain how technology plays an important role in the independent learning program in improving the quality of education. This can be seen from the implementation of independent learning policies which provide opportunities for schools, teachers, and students to innovate and have the freedom to learn independently